2019
DOI: 10.2174/1570180816666181108114115
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity, Antioxidant Properties and Phytochemical Screening of Aesculus hippocastanum Mother Tincture against Food-borne Bacteria

Abstract: Background: The advantageous health effects of extracts from different types of plants have been known for centuries and the search for new natural extracts is very important at present. Methods: In this study, the antioxidant and the antimicrobial activities of Aesculus hippocastanum mother tincture (TM) against a range of foodborne bacteria were investigated to determine the major components and the action spectrum and the antimicrobial efficacy of the extract. Results: Results demonstrated a high antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…In phytochemical assay, our study matches with [56] who reported that the methanol extract of different varieties of pomegranate had the highest phenolic content. The total phenolic content, total flavonoids, and tannins showed a proportional relationship with antioxidant values, as already observed by other authors [62]. The total phenolic content of methanolic and ethanolic extract of orange peels in this study (18.61 and 17.704 mg GAE/ml) was higher than that of [51] for the same extract (12.5 and 10.25mg GAE/ml).…”
Section: Discussionsupporting
confidence: 89%
“…In phytochemical assay, our study matches with [56] who reported that the methanol extract of different varieties of pomegranate had the highest phenolic content. The total phenolic content, total flavonoids, and tannins showed a proportional relationship with antioxidant values, as already observed by other authors [62]. The total phenolic content of methanolic and ethanolic extract of orange peels in this study (18.61 and 17.704 mg GAE/ml) was higher than that of [51] for the same extract (12.5 and 10.25mg GAE/ml).…”
Section: Discussionsupporting
confidence: 89%
“…There are also some studies in the literature regarding the antioxidant activity potential of this species. In a study investigating the antioxidant activity of A. hippocastanum mother tincture (TM), it was reported that the polyphenolic content of the sample was determined to be 506.8 mg GAEs/100 mL and exhibited significant antioxidant activity [43]. In another study evaluating the antioxidant activity of flower extracts obtained from A. hippocastanum, it was determined that the IC 50 value measured as a result of the FRAP assay was 159.82 µg/mL and a dose-related decrease in reactive oxygen species production have been determined [6].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…A Aesculus hippocastanum L. (família Sapindaceae) corresponde a uma árvore robusta popularmente conhecida como castanheiro-da-índia (Colson et al, 2019). Os extratos de suas sementes que são chamadas de castanha-da-índia, são utilizados há muitos séculos com fim terapêutico, sendo especialmente empregadas no tratamento de insuficiência venosa crônica, ulcerações, queimaduras e tratamento de inflamações na pele (Bonomo et al, 2020).…”
Section: De Acordo Comunclassified